The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1210/en.2018-00290
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of USP19 Deubiquitinating Enzyme Prevents Muscle Wasting by Modulating Insulin and Glucocorticoid Signaling

Abstract: Muscle atrophy arises because of many chronic illnesses, as well as from prolonged glucocorticoid treatment and nutrient deprivation. We previously demonstrated that the USP19 deubiquitinating enzyme plays an important role in chronic glucocorticoid- and denervation-induced muscle wasting. However, the mechanisms by which USP19 exerts its effects remain unknown. To explore this further, we fasted mice for 48 hours to try to identify early differences in the response of wild-type and USP19 knockout (KO) mice th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…We have previously shown that silencing Usp19 in skeletal muscle of WT mice leads to protection from muscle wasting due to alterations in protein turnover [14]. In addition, silencing or gene inactivation of Usp19 in muscle cells has been shown to promote their differentiation in vitro [11] or enhance insulin signalling [15], respectively. Moreover, in the present work, when SVF cells were isolated from fat from WT and Usp19 −/− mice and cultured, we observed a significant decrease in adipogenesis and fat accumulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that silencing Usp19 in skeletal muscle of WT mice leads to protection from muscle wasting due to alterations in protein turnover [14]. In addition, silencing or gene inactivation of Usp19 in muscle cells has been shown to promote their differentiation in vitro [11] or enhance insulin signalling [15], respectively. Moreover, in the present work, when SVF cells were isolated from fat from WT and Usp19 −/− mice and cultured, we observed a significant decrease in adipogenesis and fat accumulation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were generally housed in groups (maximum n = 5 per cage), but males were frequently isolated due to aggressive behaviour. Usp19 −/− mice were generated in our laboratory, as previously described [15]. Heterozygous mice (C57BL/6 background) were mated to generate WT and Usp19 −/− mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 , 14 It has been shown that USPs play important roles in the regulation of unfolded protein response and misfolding-associated protein secretion. 15 , 16 USP6 was shown to induce transcription of MMP9 through the activation of nuclear factor-κB (NF-κB) in a USP-dependent manner. 17 USP6 also induced the formation of tumors, which suggested that targeting USP6 with specific inhibitors might be an effective anticancer approach.…”
Section: Introductionmentioning
confidence: 99%
“…USP19 is involved in various cellular processes, which include endoplasmic reticulum‐associated degradation, 4 misfolding‐associated protein secretion, 5 immune response, 6 cell growth 7 and adipogenesis 8 . Importantly, USP19 has been extensively documented as an atrophy‐promoting gene in skeletal muscles 9,10 through the function of down‐regulating muscle myoblast differentiation, 11 increasing protein degradation 12 and decreasing protein synthesis 13 . In particular, depletion of USP19 in muscle myoblast increases the expression level of myogenin, which is a myogenic transcriptional factor, and this inhibits the oestradiol‐induced repression of myogenesis and promotes the synthesis of myofibrillar proteins 14 .…”
Section: Introductionmentioning
confidence: 99%